The role of silver additives in gold-mediated C–H functionalisation - Patrick, Scott R.; Boogaerts, Ine I. F.; Gaillard, Sylvain; Slawin, Alexandra M. Z.; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2011)
The role of silver additives is examined in the context of gold-mediated functionalisation of aromatic C–H bonds. Doubt is cast on the commonly cited route of halide abstraction from gold and evidence of substrate activation is given.
Keywords: C–H functionalisation; gold catalyst; halide abstraction; N-heterocyclic carbene; silver salt; substrate activation

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Rev., 2008)

(untitled) - Marion, N.; Nolan, S. P. (Chem. Soc. Rev., 2008)

(untitled) - Partyka, D. V.; Zeller, M.; Hunter, A. D.; Gray, T. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Partyka, D. V.; Updegraff, J. B., III; Zeller, M.; Hunter, A. D.; Gray, T. G. (Organometallics, 2009)

(untitled) - Gao, L.; Peay, M. A.; Partyka, D. V.; Updegraff, J. B., III; Teets, T. S.; Esswein, A. J.; Zeller, M.; Hunter, A. D.; Gray, T. G. (Organometallics, 2009)

(untitled) - Partyka, D. V.; Esswein, A. J.; Zeller, M.; Hunter, A. D.; Gray, T. G. (Organometallics, 2007)

(untitled) - Díez-González, S.; Marion, N.; Nolan, S. P. (Chem. Rev., 2009)

(untitled) - Nolan, S. P. (Acc. Chem. Res., 2011)

(untitled) - Gaillard, S.; Slawin, A. M. Z.; Nolan, S. P. (Chem. Commun., 2010)

(untitled) - Boogaerts, I. I. F.; Nolan, S. P. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, Z.; Bender, C. F.; Widenhoefer, R. A. (Org. Lett., 2007)

(untitled) - Marion, N.; Ramón, R. S.; Nolan, S. P. (J. Am. Chem. Soc., 2009)

(untitled) - Shen, K.; Fu, Y.; Li, J.-N.; Liu, L.; Guo, Q.-X. (Tetrahedron, 2007)

(untitled) - Lu, P.; Boorman, T. C.; Slawin, A. M. Z.; Larrosa, I. (J. Am. Chem. Soc., 2010)

(untitled) - Lafrance, M.; Fagnou, K. (J. Am. Chem. Soc., 2006)

(untitled) - Vechorkin, O.; Hirt, N.; Hu, X. (Org. Lett., 2010)

(untitled) - Pan, K.; Noël, S.; Pinel, C.; Djakovitch, L. (J. Organomet. Chem., 2008)

(untitled) - de Frémont, P.; Stevens, E. D.; Fructos, M. R.; Díaz-Requejo, M. M.; Pérez, P. J.; Nolan, S. P. (Chem. Commun., 2006)

(untitled) - Kanyiva, K. S.; Löbermann, F.; Nakao, Y.; Hiyama, T. (Tetrahedron Lett., 2009)

(untitled) - Whitesides, G. M.; Hackett, M.; Brainard, R. L.; Lavalleye, J.-P. P. M.; Sowinski, A. F.; Izumi, A. N.; Moore, S. S.; Brown, D. W.; Staudt, E. M. (Organometallics, 1985)